Microscopic study on the corrosion of underground pipeline - Mohamad Najmi Masri; Mohamad Fikri Samsudin; Muhammad Azwadi Sulaiman; Mazlan Mohamed; Mohamad Faiz Mohd Amin; Mohd Hazim Mohamad Amini; Mohammad Khairul Azhar Abdul Razab; Nor Hakimin Abdullah Mohamad; Bashree Abu Bakar; Muhammad Iqbal Ahmad; Nik Alnur Auli Nik Yusuf (Trans Tech Publications, 2016)
Corrosion on the water pipelines can potentially cause substantial human and economic losses. This paper concentrates on corrosion observation on the underground pipeline material as a part of our continuous study regarding this work. The samples which is mild steel taken from actually used pipeline at the site. Mild steels have been investigated intensively as a promising pipe material for underground pipeline due to their advantages such as high availability, low cost, environmental friendliness and high resistance to corrosion. However, their practical application exposes them to the attack of corrosion related to the soil condition. In this study, microscopic observations were performed on the surface of pipeline material using scanning electron microscope (SEM) and energy-dispersive x-ray (EDX) technique in order to study the morphology and basic composition of the corrosion, respectively. Based on the observation and visual analyses, it was determined that the surface of the mild steel was affected by continuous exposure to moist soil, which leads to pitting type of corrosion.